Learning ability of Thai students in affixes of Bahasa Indonesia - ., Lookman; PhD, Rosmawati Harahap (International Journal of Social Sciences and Humanities Invention, 2017)
The purpose of this study was to describe the ability to use: (1) affixation of Indonesian language; (2) to describe the misuse of language affixation, and (3) to describe the misuse of the use of affixation of the Indonesian language in the organization of Islamic student association of South Patani Thailand in Indonesia (ISASPT) academic year 2016-2017. Researcher used a descriptive method with content analysis technique that is researcher observed an object which was presented in complete and kind about everything about object being studied. The population and sample are 25 people. To collect the data, the researchers separated the essay test and multiple choices to test the respondent that is students from Thailand at the Organization of Islamic Students Association of South Patani Thailand in Indonesia (ISASPT). The ability to use affixation is 40% and the error using affixation in Indonesian is 30%. The ability to use the dominant affixation is on the results of the essay test. Twenty-five of respondents are capable to write 500 sentences that have the affixation words. The number of words that affixed is 636 words. Affix errors are in 32 words. The wrong sentence is 62 sentences with prefix are 370 in word, infix there 8 words, suffix are 76 words, confixes are 121 words, and clofixes are 61 words. Error (prefix (-di) is 8 words, prefix (me-) is 13 words, prefix (ber-) is 3 words, prefix (per-) is 1 word, prefix (ke-) 2 words), errors in confix (ke-an) is 2 words, confix (per-an) is 2 words, errors in clofix (me-i) is 1 word, clofix (memper-kan) is 2 words, and clofix (ber-kan) is 1 word. The respondents are lack to control and understand the Indonesian words. Students from Thailand at the Organization of Islamic Students Association of South Patani Thailand in Indonesia (ISASPT) as many as 25 people are able to use the Indonesian affixes but they still have misuse of prefix.